Analisis Manajemen Rantai Pasok Jahe Di Kabupaten Karanganyar - Ahmad Hartono Tanjung; Endang Siti Rahayu; Fanny Widadie (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2025)
Ginger (Zingiber officinale) is one of the leading agricultural commodities in Karanganyar Regency and makes a high contribution to the regional economy. Supply chain management is designed to face the main challenges related to quantity and quality risks and provide maximum profits for business actors. The research took place from July to August 2024. This research aims to analyze the ginger supply chain system and measure its performance using Vorst's Food Supply Chain Management (FSCN) analysis, margin value, and farmers' share. Optimization/upgrading in the supply chain is analyzed based on product, process, and functional aspects. A sampling of 35 farmers was carried out using proportional random sampling, and 8 traders used snowball sampling. The research results show that the ginger supply chain operates well through four distribution channels. Channel I (Farmers-consumers), Channel II (Farmers-retailers-consumers), Channel III (Farmers-collectors-retailers), Channel IV (Farmers-collectors-industrial consumers). Channel I is the most efficient with a margin value of zero and a farmer's share value of 100%. The highest margin value is in channel III at Rp. 4,428.60. Recommendations for product, process, and functional upgrading include improving land management, such as superior seeds; increasing control of storage space; improving the contract system; creating website technology; and government support in meeting the needs of chain members (capital, credit, and institutional formation). The aim is to increase the efficiency, effectiveness, and competitiveness of ginger to gain a wider market share.